ADVANCED NETWORK SECURITY CONCEPTS: NETWORK SEGMENTATION AND ZERO TRUST ARCHITECTURE - Amod Darshane (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article explores two critical concepts in enterprise networking and security: Network Segmentation and Zero Trust Architecture (ZTA). It examines their principles, implementation methods, and benefits in the context of evolving cyber threats and complex IT environments. The article delves into the technical aspects of Network Segmentation, including VLANs, next-generation firewalls, and software-defined networking, as well as the core components of ZTA such as identity and access management, micro-segmentation, and continuous monitoring. The article also analyzes the synergies between these two approaches, demonstrating how their integration can create a robust, multi-layered security strategy. Through comparative analysis and case studies, the article provides network professionals with comprehensive insights to enhance their organizations' security posture, offering a framework for implementing these advanced security concepts in modern enterprise environments.